(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3Gdbhd ai JChjd bhdg Ld KfGDg (B" (3hEP bGd ehSi daJGg dG CHQM MJi CHdZ eLeY GdHMQjf Ch CbVi MbHkG (B" s
(3BNQgG (B:s
" (3aef cGf jQLh dbGA QHg adjYed YedkG UGdMkG hdG jTQc HYHGOI QHg CMOkG (B" (3hbGd EfgG BNQ BjI fRdJ ef GdbQB f JMJ ShQI Gdcga Je GdSaQ HMeO Gddg s
(3bWYI ai JaSjQ ChGNQ ShQI Gdcgas
(3fSNI Ydi Qa ZRGd ef JMHjS GdSdWGf CHh YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(791 / 40) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs